UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN MATEMATIKA MELALUI METODE SNOWBALL THOROWING PADA SISWA KELAS XII.IPA2 SMA NEGERI 1 KINALI - Nuridha Nuridha (JURNAL MANAJEMEN PENDIDIKAN, 2017)
Based on the results of student learning XII.IPA2 Class SMA N 1 Kinali in Mathematics was found that results for students in the subjects of Mathematics is still very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about the efforts to improve student learning outcomes in mathematics sub Specifies the nth row and the sum of n term of arithmetic and geometry through Thorowing Snowball Method in class XII.IPA2 SMA N 1 Kinali West Pasaman .This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of 36 students Grades XII.IPA2 SMA N 1 Kinali. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the Snowball Method Thorowing can improve student learning outcomes in mathematics sub Specifies the nth row and the sum of n term of arithmetic and geometry in high school N 1 Kinali. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 46.69 (Not Good) increased to 83.86 (Good) with an increase of 37.17%.